If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -4x = -36 Combine like terms: 7x + -4x = 3x 3x = -36 Solving 3x = -36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '3'. x = -12 Simplifying x = -12
| 5-7x-8+14x-17=10x-4x-3 | | 6x+8=-37-3x | | 1-3k-13=30 | | 5-7x-8+14x-17=11-2+5+28-10+18 | | 2X^4+3X^3+X^2=0 | | x-y=3*x-y | | -14k-10k=24 | | -2(p+1)=-5-p | | 12=-b-3b | | 5d-7=2-4d | | 3(3-10x)=25(x+2) | | 2x^6+9x^3-5=0 | | 3*a-b=90 | | x+5*(3x+10)+10=2 | | -12a+10a=-22 | | 21-2x*3=5 | | 5(3y-13)-4y=-21 | | -6m-10m=-16 | | -24=5b+b | | -25=-10x+5x | | -8n-n=-18 | | 14x-25=12x+25 | | 2n+2+4n=2 | | 6x-1=5x+6 | | -11k+9k=-20 | | -11-2k=1+k | | 4b+10b=28 | | 2(k-3)=6 | | n-13+5n=-25 | | 4u-8=-28 | | x-7-12x=37 | | (14)-(-4)= |